The preliminary study of oil removal using lemon peel waste / Nur Syahirah Amirah Mohd Jopery ... [et al.] - Mohd Jopery, Nur Syahirah Amirah; Abdullah, Mohammad; Soo, Kum Yoke; Mustaffa, Ahmad Rozaimee (Universiti Teknologi MARA, 2020)
While the discovery of oil contributes a lot towards a country's economy and technological development, it is also the cause for oil pollution. As such, this study proposes to use lemon peel waste as a low-cost adsorbent to manage oil pollution. For the untreated adsorbent, the lemon peels were cut into small pieces and dried under sunlight for 48 hours. Then, it was further dried in an oven for 24 hours and ground into powder. For the treated adsorbent, the lemon peels were soaked in 0.5 M of sodium hydroxide (NaOH) solution. The adsorbent was used to adsorb different types of oil (diesel oil, lubricant oil, waste vegetable oil) and in different types of water (ocean water, lake water, tap water) with different amounts of adsorbent which is 0.2 g, 0.4 g, 0.6 g, 0.8 g, and 1.0 g for adsorbent dosage experiment. While for types of water experiment, a ratio for volume of water and oil of 3:1, and constant mass adsorbent was used. The result showed that untreated adsorbent can adsorb higher amount of oils than treated adsorbent. The oil that could be easily adsorbed using lemon peels adsorbent is diesel oil with 89.91% adsorption. For the types of water, the result changes according to different types of water and oil used. It was found that the higher the mass adsorbent, the lower the percentage of oil removal. The highest percentage of diesel oil removed in ocean water is 81.68%. While the removal of lubricant oil and waste vegetable oil in lake water is 66.6% and 72.13%, respectively. Scanning Electron Microscopy (SEM) shows that treated lemon peels had small pores compared to untreated lemon peel waste. This study demonstrated and proposed that the lemon peel waste has a good potential in low-cost oil waste removal.